Atrioesophageal Fistula: Clinical Presentation, Procedural Characteristics, Diagnostic Investigations, and Treatment Outcomes. (November 2017) - Han, Hui-Chen; Ha, Francis J.; Sanders, Prashanthan; Spencer, Ryan; Teh, Andrew W.; O'Donnell, David; Farouque, Omar; Lim, Han S.
Abstract : Background: Percutaneous or surgical ablation are increasingly used worldwide in the management of atrial fibrillation. The development of atrioesophageal fistula (AEF) is among the most serious and lethal complications of atrial fibrillation ablation. We sought to characterize the clinical presentation, procedural characteristics, diagnostic investigations, and treatment outcomes of all reported cases of AEF. Methods and Results: Electronic searches were conducted in PubMed and Embase for English scientific literature articles. Out of 628 references, 120 cases of AEF were identified using various ablation modalities. Clinical presentation occurred between 0 and 60 days postablation (median 21 days). Fever (73%), neurological (72%), gastrointestinal (41%), and cardiac (40%) symptoms were the commonest presentations. Computed tomography of the chest was the commonest mode of diagnosis (68%), although 7 cases required repeat testing. Overall mortality was 55%, with significantly reduced mortality in patients undergoing surgical repair (33%) compared with endoscopic treatment (65%) and conservative management (97%) (adjusted odds ratio, 24.9; P <0.01, compared with surgery). Multivariable predictors of mortality include presentation with neurological symptoms (adjusted odds ratio, 16.0; P <0.001) and gastrointestinal bleed (adjusted odds ratio, 4.2; P =0.047). Conclusions: AEF complicating atrial fibrillation ablation is associated with a high mortality. Clinicians should have a high suspicion for the development of AEF in patients presenting with infective, neurological, gastrointestinal, or cardiac symptoms within 2 months of an atrial fibrillation ablation. Investigation by contrast computed tomography of the chest with consideration of repeat testing can lead to prompt diagnosis. Surgical intervention is associated with improved survival rates. Abstract : Supplemental Digital Content is available in the text.